The synthesis and photophysicochemical behaviour of novel water-soluble cationic indium(III) phthalocyanine - Durmus, Mahmut; Erdogmus, Ali; Ogunsipe, Abimbola; Nyokong, Tebello (ELSEVIER SCI LTD, 2009)
The syntheses and characterization of 2,3-octakis-(3-pyridyloxyphthalocyaninato) indium(III) and quaternized 2,3-octakis-(3-pyridyloxyphthalocyaninato) indium(III) are described. The ground state electronic absorption spectra, photophysics and photochemistry of both dyes in DMSO as well as that of the quaternized compound in aqueous solution are also presented. A comparison of the photophysical and photochemical parameters of the two dyes revealed that quaternized 2,3-octakis-(3-pyridyloxyphthalocyaninato) indium(III) was a better photosensitizer than its unquaternized counterpart. The quantum yield values of fluorescence (Phi(F)), triplet state formation (Phi(T)) and singlet oxygen formation (Phi(Delta)) for the cationic dye were found to be 0.03, 0.68 and 0.66 respectively in DMSO; these values were higher than those for 2,3-octakis-(3-pyridyloxyphthalocyaninato) indium(III), which exhibited values of 0.02, 0.66 and 0.63, respectively in DMSO. The values for the cationic dye in aq. solution were 0.02, 0.59 and 0.56 respectively, suggesting that the water-soluble quaternized 2,3-octakis-(3-pyridyloxyphthalocyaninato) indium(III) offers potential as a photosensitizer in photodynamic therapy treatment. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Indium(III) phthalocyanine; Synthesis; Photophysics; Photochemistry; Photodynamic therapy; Singlet oxygen; QUANTUM YIELDS; SUBCELLULAR-LOCALIZATION; PHOTOCHEMICAL PROPERTIES; ZINC PHTHALOCYANINE; FLUORESCENCE; METAL; STATE; COMPLEXES; PORPHYRIN; Chemistry; Engineering; Materials Science